Factors Affecting Organizational Performance Of Smes In Uae - Saoud Khalid Humaid, Alqasimi Shaikh Abdulaziz (2022)
SMEs are regarded as a vital component of any economy regardless of the development status. This study considers the role of entrepreneurial leadership (EL), learning orientation (LO) and digital transformation in determining the business performance (OP) for the Small and Medium Enterprises as working in Dubai, UAE with Digital strategy as moderator and innovation capacity as mediator as dipcited in Figure 2.1. For this purpose, primary data was collected with the help of questionnaire as developed through extracting the various items from existing literature for the study variables. With the help of probability sampling, a valid sample of 400 respondents was collected and empirically analyzed. Furthermore, based on the deductive approach, current study has tested the relationship between the variables through two step approach which is entitled as measurement model assessment and structural model assessment, respectively. The findings through measurement model assessment specify that there is no problem for the reliability, internal consistency, and other measurements which are necessary while going for the structural model assessment.